2020
DOI: 10.3390/ijms21103515
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Fluid Cytokines Reveal New Insights of Endometriosis Subphenotypes

Abstract: Endometriosis is a common inflammatory gynecological disorder which causes pelvic scarring, pain, and infertility, characterized by the implantation of endometrial-like lesions outside the uterus. The peritoneum, ovaries, and deep soft tissues are the commonly involved sites, and endometriotic lesions can be classified into three subphenotypes: superficial peritoneal endometriosis (PE), ovarian endometrioma (OE), and deep infiltrating endometriosis (DIE). In 132 women diagnosed laparoscopically with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 80 publications
2
43
0
Order By: Relevance
“…More recent studies consider the chronic inflammatory response as an important part of the pathomechanism of this disease. Initially, it may appear as an increased influx of cells, followed by an acute inflammatory process that involves the local vasculature, a specific cytokine profile, and the recruitment of immunocytes [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies consider the chronic inflammatory response as an important part of the pathomechanism of this disease. Initially, it may appear as an increased influx of cells, followed by an acute inflammatory process that involves the local vasculature, a specific cytokine profile, and the recruitment of immunocytes [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that cytokine analysis of peritoneal fluids could differentiate women diagnosed and stratified laparoscopically with ovarian endometrioma, peritoneal endometriosis, or deep infiltrating endometriosis. This suggests that certain cytokine signatures could be driving different biological signaling events and immune responses in these patients ( Zhou et al, 2020 ).…”
Section: Mechanisms Underlying Endometriosis Induced Painmentioning
confidence: 99%
“…It occurs in 10% of women of reproductive age, 1,2 causing chronic pelvic pain and infertility. Half of the women with infertility have endometriosis 3 …”
Section: Introductionmentioning
confidence: 99%
“…The lesions can manifest as follows: superficial peritoneal implants (SPIs) in the pelvic peritoneum or pelvic organs, ovarian cysts or endometriomas, and deep infiltrating endometriosis (DIE) referring to lesions that invade the organs, such as the bladder and bowel. Interestingly, superficial lesions can have different colors on laparoscopy (white, red, or black) depending on the time that the endometriosis occurred 3 . SPIs are regulated by peritoneal fluid‐related factors, while endometriomas and DIE may be influenced by ovarian‐ and blood‐related factors 4…”
Section: Introductionmentioning
confidence: 99%